Effect of Sandalwood Aromatherapy In Sleep Quality of Adolescents At Dharma Jati Orphanage II In The Year 2012 - Ni Wayan Nanik Ariani (Coping: Community of Publishing in Nursing, 2013)
Adolescence is a level of growth and development when the speed is almost same as baby. In this level of development, adolescents need more time to sleep thus their bodies can do the internal work. The changes of puberty and internal clock of adolescents impact adolescents to feel sleepy until 11 pm or more and gets minimum nine hours as night recommended. Lack of sleep that occurs in adolescence will affect their growth. Secretion of growth hormone work at the highest level during sleep. Sleeping problems that occur in adolescents can be solved by using aromatherapy. Aromatherapy is a kind of complementary therapy which help adolescents to sleep by give a relaxing effect on muscles. This study aims to determine the effect of giving sandalwood aromatherapy towards adolescents sleep quality. The method that’s used in this study were pre-experimental with one group pretest-posttest design design. Samples were of 22 people who was obtained through a total sampling technique. Collecting data be done through an interview with questionnaire The SMH (St. Mary's Hospital Sleep) and observation. The results obtained before the experiment is 13.6% of adolescents have well-qualities of sleep, 86.4% of adolescents have moderate quality of sleep. After experiment results is 45.5% of adolescents have well-qualities of sleep, 54.5% well-qualities of sleep. moderate qualities of sleep. Sandalwood aromatherapy impact on improving the adolescents quality of sleep. Statistical tests used were the Wilcoxon Signed Rank Test (p ? 0.05). The result of after data analysis, is (p=0.000) which means there is effect of giving sandalwood aromatherapy against adolescent quality of sleep. Based on these results, sandalwood aromatherapy can be used to adolescents who experience sleeping problems at comunity, so it is recommended for nurses to use sandalwood aromatherapy as an alternative therapy in the treatment of adolescents sleeping problems.